A Comparative study on the role of institutions in promotion of foreign direct investment - BANDA, Elita (KDI School, 2015)
Resource poor countries depend on international trade for economic and social development. Countries that do not have domestic exporting industries attract foreign investors to help start and grow such industries. Together with integrating an economy into the world market, foreign direct investment (FDI) brings with it a number of other spillovers such as; technology and know-how transfers and human capital enhancement. These spillovers, however, do not happen automatically. They depend much on the domestic environment and the types of institutions present to facilitate the spillovers into the domestic economy. Mauritius; a country seen by many as an African success story, made a lot of economic and social gains from its textile exporting industry which came into the country through foreign direct investment. It ranks 1st on the African Governance Index and has one of the highest per capita GDP in Africa. Much of Mauritius’ success is attributed to the quality of its institutions. Lesotho; a least developed African country received foreign investments in the textile industry around the same time Mauritius did. However, today the situations in the two countries are very different. This paper takes a comparative look at the two countries to see what roles institutions played in facilitating spillovers from the foreign owned textile industries. We see that in Mauritius much effort was made to facilitate exports through the creation of an export processing zone (EPZ), to enhance human capital through vocational training and to facilitate the domestic ownership of the textile industry. When we examine the case of Lesotho we find that there is little if any local ownership of the industry. Learning and Vocational training infrastructure that feeds the needs of this industry is non-existent and efforts to promote entrepreneurship to create linkages have since failed. This lackluster performance, this paper attributes to the type of institutions that prevail in Lesotho, extractive political and economic institutions that do not work for the benefit of the country and its people
Thesis(Master) --KDI School:Master of Development Policy,2015